(untitled) (Research, Society and Development, 2020)
The rapid and disordered urban growth generated an artificial geographic environment and low environmental health, characterized by the expansion of peripheral and central areas. The transformations in land use and occupation generate changes in the energy balance and atmosphere, resulting in the heating of cities. Therefore, the objective of this article is to analyze the Earth’s Surface Temperature (TST) and relate with vegetation cover through the Normalized Difference Vegetation Index (NDVI) in the city of Fortaleza, Ceará. Initially, orbital images, OLI (Operational Land Imager) and TIRS10 (Thermal Infrared Sensor) of landsat-8 were obited in the United States Geological Survey (USGS) – orbit 217 and point 62. The images chosen for this study are from 02/08/2013 and 26/08/2016. It was verified the direct relationship of biomass vigor (NDVI) and urbanization with surface temperature values and urban heat islands. The environments with the lowest NDVI values, with the exception of aquatic bodies, presented higher temperature values, exposing the importance of vegetation in the microclimate.